Changes in Serum Iron, Total Iron Binding Capacity and Transferrin Saturation Percent in Sudanese Females Newly Diagnosed with Breast Cancer at Khartoum Oncology Hospital: A case- control study - Rufaida Mustafa Ahmed Mustafa; Nazik Elmalaika Obaid Seid Ahmed Husain (Sudan Journal of Medical Sciences)
Background:Iron is a vital constituent of cells but in excess may be harmful and is associated with a raised risk for some malignant diseases including breast cancer. We aimed to study changes in iron profile in Sudanese females newly diagnosed with breast cancer.